Randomized clinical trial of perioperative omega-3 fatty acid supplements in elective colorectal cancer surgery. Issue 2 (26th November 2013) - Sorensen, L S; Thorlacius-Ussing, O; Schmidt, E B; Rasmussen, H H; Lundbye-Christensen, S; Calder, P C; Lindorff-Larsen, K
Abstract: Background: Omega-3 fatty acids ( n -3 FAs) may have beneficial clinical effects, and n -3 FA supplements may improve outcome after surgery. Methods: In a randomized double-blind placebo-controlled trial in single centre, patients referred for elective colorectal cancer surgery received either an n -3 FA-enriched oral nutritional supplement (ONS) (Supportan®, 200 ml twice daily) providing 2·0 g eicosapentaenoic acid (EPA) and 1·0 g docosahexaenoic acid (DHA) per day, or a standard isocaloric and isonitrogenous ONS, for 7 days before and 7 days after surgery. The primary endpoint was infectious and non-infectious complications within 30 days of surgery. Secondary endpoints were length of hospital stay, intensive care unit admission, readmissions, and concentrations of marine n -3 FAs and arachidonic acid in granulocyte membranes. Results: Some 148 consecutive patients (68 women, 80 men; mean age 71 (range 41–89) years) were randomized. There was no significant difference between groups in infectious or non-infectious postoperative complications ( P = 1·000). Granulocyte levels of EPA, DHA and docosapentaenoic acid (DPA) were significantly higher in the n -3 FA-enriched supplement group compared with the control group ( P < 0·001). The arachidonic acid level in granulocytes was significantly lower in the enriched group than in the control group ( P < 0·001). Conclusion: EPA, DHA and DPA were incorporated into granulocytes in patients receiving n -3 FAs, but this was not associated with improved postoperative outcomes. Registration number: NCT00488904 (http://www.clinicaltrials.gov ). Abstract : Immunonutrition did not alter outcomes